2017
DOI: 10.3390/rs9050453
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Urbanization Dynamics and its Impacts on Surface Heat Islands: A Case Study of Beijing, China

Abstract: Abstract:As the capital of China, Beijing has experienced a continued and rapid urbanization process in the past few decades. One of the key environmental impacts of rapid urbanization is the effect of urban heat island (UHI). The objective of this study was to estimate the urbanization indexes of Beijing from 1992 to 2013 based on the stable nighttime light (NTL) data derived from the Defense Meteorological Satellite Program's Operational Line Scanner System (DMSP/OLS), which has became a widely used remote s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Dynamics of land cover and land use over time are of equal importance in shaping the SUHI patterns. For example, urban growth can increase the SUHI extent and intensity [95,149,151,152] by increasing proportions of built-up land and decreasing proportions of vegetated areas, especially in the earlier stages of urbanization [90] and/or regions undergoing rapid land cover and land use change [116].…”
Section: Suhi Variations At a Local Scale And Their Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamics of land cover and land use over time are of equal importance in shaping the SUHI patterns. For example, urban growth can increase the SUHI extent and intensity [95,149,151,152] by increasing proportions of built-up land and decreasing proportions of vegetated areas, especially in the earlier stages of urbanization [90] and/or regions undergoing rapid land cover and land use change [116].…”
Section: Suhi Variations At a Local Scale And Their Driversmentioning
confidence: 99%
“…The Landsat archive has provided LST observations for more than 30 years at a high spatial resolution, but the long revisiting cycle impedes the wide application in detecting the SUHI's inter-annual variability of SUHI [119,213]. As a result, the previous efforts focused mainly on the impacts of urban expansion on LST using the data in a few representative years and days of the year [88,90,[252][253][254][255]. The increasing duration of the MODIS LST record, with high temporal resolution and data quality, allow us to examine both inter-annual variability and long-term trends of SUHI after 2000.…”
Section: Interannual Variability and Long-term Trends Of Suhimentioning
confidence: 99%
“…With the advantages of high spatial and temporal resolution, availability, and free and easy access, numerous studies of UHI have been based on LST that were observed from satellite imagery [12]. For UHI studies at the local scale, thermal data (including Landsat 5 TM and Landsat 8 OLI with spatial resolutions of 120 and 100 m, respectively) were widely used [13].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid urbanization process plays a key role in the heating phenomenon known as urban heat island (UHI) [1], involving both air and surface temperatures in different ways [2]. The UHI has effects on human comfort, air pollution, energy management, urban planning policy, and climate changes [3][4][5][6][7]. In fact, land surface temperature (LST) images retrieved from satellite sensor thermal observations, from which UHI maps are derived, supply a scientific support to assess if the urban development model is compliant with the environmental sustainability [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%